Influence of Crack Spacing/Layer Thickness Value on Reflection Crack Propagation Mechanism Under Low Temperatures - Bao, Chunyan; Liu, Qi; Xia, Yingjie; Cui, Yi; Cao, Zongyong; Qian, Yidong; Liu, Minghao; Mu, Chaoqian; Wang, Hongliang (Frontiers in Earth Science, 2022)
The pavement structure damage caused by the reflection cracks of asphalt concrete pavement structures is an urgent problem to be solved in many regions of China. Especially in the cold regions of China, it is more serious, so it is necessary to study how to reduce the probability of reflective cracking and reduce the damage to asphalt pavement structures. In this paper, the acoustic emission detection method is used to study the acoustic emission characteristics of pavement structures and the crack propagation law inside the structure. On this basis, cracks with S/T values of 1.25, 2.5, 3.75 and 5 were prefabricated in the base layer by numerical simulation method. The models with different base crack spacing were calculated by RFPA finite element software, and the influence of different crack spacing on the propagation mechanism of reflective cracks in the base structure was studied. The results show that the AC pavement structure has obvious acoustic emission characteristics. The faster the cooling rate is, the more serious the damage to the surface layer of the AC pavement structure is. In addition, with the increase of S/T value, the stress level between cracks increases continuously, but most of the stress will make the cracks expand towards the grassroots structure, and only a small part of the stress is used to form the reflective cracks. In practical engineering, it is suggested to increase the crack resistance of base materials and preset some small spacing cracks in the large spacing cracks in the base.